Hemodilution and Serum Progesterone Regulation in Males with Obesity - Shen SW; You JJ; Xu XY; Zhang P; Song C; Shen ZH; Li F (Journal of Inflammation Research, 2025)
Shi-wei Shen,1,* Jing-jie You,2,* Xiao-ying Xu,2,* Ping Zhang,2,* Cheng Song,2,* Zhen-hai Shen,2 Feng Li2 1Department of Endocrinology, The Second People’s Hospital of Wuxi, Central Hospital Affiliated to Jiangnan University, Wuxi, Jiangsu, People’s Republic of China; 2Health Management Center, Taihu Rehabilitation Hospital of Jiangsu Province, Wuxi, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Feng Li, Health Management Center, Taihu Rehabilitation Hospital of Jiangsu Province, Inside YuanTouZhu Park, Binhu Distinct, Wuxi, Jiangsu, People’s Republic of China, Tel +86-15061840441, Email lifeng_lf98@outlook.com Zhen-hai Shen, Health Management Center, Taihu Rehabilitation Hospital of Jiangsu Province, Inside YuanTouZhu Park, Binhu Distinct, Wuxi, Jiangsu, People’s Republic of China, Tel +86-13812040177, Email shenzhenhaiszh@126.comObjective: This study aimed to examine the correlation between serum progesterone levels, body mass index (BMI), and hemodilution in males, with an emphasis on the potential influence of lymphocyte counts.Methods: A retrospective analysis was conducted on two cohorts comprising of 83 and 139 participants, respectively. Data collected included age, BMI, plasma volume, and serum progesterone levels. Plasma volume was estimated using a standardized formula, and multivariate regression models calibrated for age were used to assess the effects of BMI on plasma volume, progesterone levels, and lymphocyte counts.Results: An inverse association was identified between BMI and serum progesterone concentrations, likely attributable to hemodilution, while systemic progesterone load remained consistent across BMI categories. A positive correlation was observed between lymphocyte counts and serum progesterone levels, suggesting an inflammatory component influencing progesterone regulation.Conclusion: These findings suggest that hemodilution and inflammation (the latter indicated by lymphocyte counts) may modulate serum progesterone levels in obese males. These observations could have potential clinical implications for hormonal health and highlight the need for further research into the underlying mechanisms.Keywords: cross-sectional study, hemodilution, lymphocyte counts, obesity, progesterone